2016
DOI: 10.3109/17453674.2016.1173982
|View full text |Cite|
|
Sign up to set email alerts
|

Periprosthetic tibial bone mineral density changes after total knee arthroplasty

Abstract: Background and purposeTotal knee arthroplasty (TKA) may cause postoperative periprosthetic bone loss due to stress shielding. Bone also adapts to mechanical alterations such as correction of malalignment. We investigated medium-term changes in bone mineral density (BMD) in tibial periprosthetic bone after TKA.Patients and methods86 TKA patients were prospectively measured with dual-energy X-ray absorptiometry (DXA), the baseline measurement being within 1 week after TKA and the follow-up measurements being at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 24 publications
(34 reference statements)
2
42
1
Order By: Relevance
“…Trabecular bone distal to metal-backed tibial trays has been shown to be more stress shielded than all-polyethylene implants using computational modeling (Thompson, Yohuno et al 2015). Changes in peri-prosthetic tibial bone density may not always lead to complications, with good clinical outcomes achievable (Jaroma, Soininvaara et al 2016). The importance of the cement-bone interface in achieving stable initial fixation cannot however be understated.…”
Section: Introductionmentioning
confidence: 99%
“…Trabecular bone distal to metal-backed tibial trays has been shown to be more stress shielded than all-polyethylene implants using computational modeling (Thompson, Yohuno et al 2015). Changes in peri-prosthetic tibial bone density may not always lead to complications, with good clinical outcomes achievable (Jaroma, Soininvaara et al 2016). The importance of the cement-bone interface in achieving stable initial fixation cannot however be understated.…”
Section: Introductionmentioning
confidence: 99%
“…After TKA, the bone density around the prosthesis decreased, and the medial side decreased more than the lateral side. In fact, the decrease in BMD following TKA had been widely reported and was generally believed to be the result of a biomechanical response to stress shielding of the tibial component [8,[22][23][24][25][26]. Surgery altered the intra-articular environment and osteotomy exposed cancellous bone.…”
Section: Discussionmentioning
confidence: 99%
“…The signi cant in uence of activity level on rBMD after 1 and 3 years could be attributed to adaptive bone remodeling and changes in load, as Jaroma, A et al reported that tibial metaphyseal periprosthetic bone was remodeled after TKA due to mechanical axis correction [8]. However, the postoperative activity level had no signi cant effect on BMD after 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative changes in the periprosthetic bone density in the tibia are closely related to the outcomes of TKA. Several studies [4][5][6][7] have reported a reduction in BMD in the proximal tibia after TKA, which can cause the subsidence of some components, especially of the tibial plateau, and increase the risk of prosthetic loosening and further revision.…”
Section: Introductionmentioning
confidence: 99%